Practical robustness evaluation in radiotherapy – A photon and proton-proof alternative to PTV-based plan evaluation. (December 2019) - Korevaar, Erik W.; Habraken, Steven J.M.; Scandurra, Daniel; Kierkels, Roel G.J.; Unipan, Mirko; Eenink, Martijn G.C.; Steenbakkers, Roel J.H.M.; Peeters, Stephanie G.; Zindler, Jaap D.; Hoogeman, Mischa; Langendijk, Johannes A.
Highlights: A practical method is described to assess robustness of CTV dose in both photon and proton treatments. By a calibration procedure consistency with historic PTV-based evaluations is achieved. The method has been clinically introduced in the Dutch proton centres and replaced PTV-based evaluations, solving its inaccuracies caused by the 'static dose cloud approximation'. Abstract: Background and purpose: A planning target volume (PTV) in photon treatments aims to ensure that the clinical target volume (CTV) receives adequate dose despite treatment uncertainties. The underlying static dose cloud approximation (the assumption that the dose distribution is invariant to errors) is problematic in intensity modulated proton treatments where range errors should be taken into account as well. The purpose of this work is to introduce a robustness evaluation method that is applicable to photon and proton treatments and is consistent with (historic) PTV-based treatment plan evaluations. Materials and methods: The limitation of the static dose cloud approximation was solved in a multi-scenario simulation by explicitly calculating doses for various treatment scenarios that describe possible errors in the treatment course. Setup errors were the same as the CTV-PTV margin and the underlying theory of 3D probability density distributions was extended to 4D to include range errors, maintaining a 90% confidence level. Scenario dose distributions were reduced to voxel-wise minimum and maximum dose distributions; the first to evaluate CTV coverage and the second for hot spots. Acceptance criteria for CTV D98 and D2 were calibrated against PTV-based criteria from historic photon treatment plans. Results: CTV D98 in worst case scenario dose and voxel-wise minimum dose showed a very strong correlation with scenario average D98 (R 2  > 0.99). The voxel-wise minimum dose visualised CTV dose conformity and coverage in 3D in agreement with PTV-based evaluation in photon therapy. Criteria for CTV D98 and D2 of the voxel-wise minimum and maximum dose showed very strong correlations to PTV D98 and D2 (R 2  > 0.99) and on average needed corrections of −0.9% and +2.3%, respectively. Conclusions: A practical approach to robustness evaluation was provided and clinically implemented for PTV-less photon and proton treatment planning, consistent with PTV evaluations but without its static dose cloud approximation.